Chlorination Strategy‐Induced Abnormal Nanomorphology Tuning in High‐Efficiency Organic Solar Cells: A Study of Phenyl‐Substituted Benzodithiophene‐Based Nonfullerene Acceptors. Issue 11 (25th July 2019) - Yan, Cenqi; Yang, Tao; Gao, Wei; Xiao, Yiqun; Li, Yuhao; Lu, Xinhui; Yang, Chuluo; Li, Gang
Abstract : A new heptacyclic core based on phenyl‐substituted benzo[1, 2‐ b :4, 5‐ b' ]dithiophene (BDT) is designed and paired with 1, 1‐dicyano methylene‐ 3 ‐indanone (INCN) end group to construct a nonfullerene acceptor, BPIC. The strong aggregation and large phase separation in the poly[(2, 6‐(4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)‐benzo[1, 2‐ b :4, 5‐ b ′]dithiophene))‐alt‐(5, 5‐(1′, 3′‐di‐2‐thienyl‐5′, 7′‐bis(2‐ethylhexyl)benzo[1′, 2′‐c:4′, 5′‐c′]dithiophene‐4, 8‐dione))]) (PBDB‐T):BPIC blend cause inefficient exciton dissociation and ineffective charge transport, resulting in a low 11.12% power conversion efficiency (PCE) with low short‐circuit current density ( J SC ) and fill factor (FF). To finely control the active‐layer nanomorphology, the chlorine atom is introduced into the INCN termini, and di‐chlorinated BPIC‐2Cl and tetra‐chlorinated BPIC‐4Cl are synthesized. It is an interesting phenomenon that, unlike other literature reports, while the di‐chlorination reduces crystallinity and phase‐separation scale, further chlorination increases crystallinity and phase separation. The PBDB‐T:BPIC‐2Cl device exhibits suitable molecular packing and nearly ideal nanoscale phase separation, which facilitates exciton dissociation and charge transport and thus yields the higher PCE of 12.63% with significantly improved J SC and FF. PBDB‐T:BPIC‐4Cl device, however, exhibits strong stacking intensity and excessively large phase separation, leading to the clearly reduced J SC, FF, and PCE of only 8.23%. This work demonstrates that novel phenyl‐substituted BDT core and delicated chlorination strategy provides powerful tools for high‐performance nonfullerene acceptors in organic solar cells. Abstract : Three novel low‐bandgap fused‐ring electron acceptors, BPIC, BPIC‐2Cl, and BPIC‐4Cl are designed based on a heptacyclic core, using phenyl‐substituted benzo[1, 2‐ b :4, 5‐ b′ ]dithiophene as the central unit, end‐capped with 1, 1‐dicyano methylene‐3‐indanone (INCN), mono‐chlorinated INCN, and di‐chlorinated INCN moieties, respectively. The effects of chlorination on optical and electronic properties of molecules, film morphology, and photovoltaic device performance are investigated.